Non-NMDAR neuronal Ca2+–permeable channels in delayed neuronal death and as potential therapeutic targets for ischemic brain damage. (July 2015) - Li, Chaokun; Meng, Li; Li, Xin; Li, Dongliang; Jiang, Lin-Hua
<x xml:space="preserve">Abstract</x> Introduction: Transient cerebral ischemia represents the most common cause of complex chronic disability in adults due to delayed neuronal death as a result of aberrant post-ischemic increases in the [Ca2+]c and [Zn2+]c. A number of Ca2+-permeable channels are engaged in transient ischemia-induced neuronal death. Areas covered: In this review, the authors discuss the GluA2-lacking AMPARs, acid-sensing ion channel 1a, melastatin-related transient receptor potential 2 (TRPM2), TRPM7 and store-operated Ca2+ channels expressed in ischemia-vulnerable neurons, and focus on the studies using in vitro and in vivo models of transient ischemia that supports a significant role for these channels in inducing increases in the [Ca2+]c and/or [Zn2+]c and delayed neuronal death, and their potential as therapeutic targets. Expert opinion: Non-NMDAR Ca2+-permeable channels are important mechanisms mediating delayed neuronal death and cognitive dysfunctions after transient ischemia. Identification of such Ca2+-permeable channels significantly improves our understanding of the molecular events leading to ischemic brain damage and provides promising novel targets for post-ischemic therapeutics treating ischemic brain damage.